First-principles calculations of electronic structures and optical, phononic, and thermodynamic properties of monoclinic α-spodumene. Issue 8 (1st June 2017) - Yonghua, Duan; Lishi, Ma; Ping, Li; Yong, Cao
Abstract: To further the applications of spodumene in ceramic materials, we performed first-principles density functional theory calculations using a quasi-harmonic approximation to investigate the electronic structures and optical, phononic, and thermodynamic properties of monoclinic types of α -spodumene with C 2 and P 21 structures. The electronic structures of C 2- and P 21 -spodumene including band structure and density of states, were observed to be similar. These spodumene can be treated as wide-direct-band-gap insulators with band-gap widths of 5.537 eV for C 2 -spodumene and 6.335 eV for P 21 -spodumene. The optical properties of C 2- and P 21 -spodumene indicated that both C 2- and P 21 -spodumene were found to be optically anisotropic and they can be used for UV shielding in optical devices. Additionally, we investigated the phononic properties of these spodumene to explore their thermodynamic characteristics, and found that both types are dynamically stable.